Real-time Business Intelligence Platform to maternity care - Brandão, Andreia (2014)
The motivation for the implementation of a decision support system in maternity care came from the fact that people are constantly making quick decisions based on incomplete information. There is a significant impact on the patient health, as well as in increasing medical errors. To implement this system, it was resorted to the technologies of Business Intelligence, which involved the construction of two data warehouses with a dimensional structure in a star shape, for two distinct modules, in Gynecology and Obstetrics cares. The feasibility of an evidence-based practice and medical decision making in real time with universal and interoperable features are some of the benefits resulting from the implementation of decision support system in maternity care. In this paper we present the architecture of BI solution, some clinical outcomes and some benefits of the BI solution in a real world context.